Answer:
[tex]\underline{\underline{ -10x +2}}[/tex]
Step-by-step explanation:
A expression is given to us and we need to simplify out the expression . The given expression is ,
[tex]\implies 2(-3x +1)-4x [/tex]
Open the brackets .
[tex]\implies -6x +2-4x [/tex]
Simplify the like terms .
[tex]\underline{\underline{ -10x +2}}[/tex]
Hence the correct option is (4) .
The population of a city has increased by 27% since it was last measured. If the current population is 38,100, what was the previous population?
=___
Answer:
the previous population was 62,000.
Step-by-step explanation:
The current population of a city = 83,700
The population of a city has increased by 35% since it was last measured.
We have to calculate the previous population before increasing 35%.
Let the previous population be p
p +(35% × p) = 83,700
p + 0.35p = 83,700
1.35p = 83,700
p =
p = 62,000
Therefore, the previous population was 62,000.
The population of a city has increased by 27% since it was last measured and the previous population was 62,000.
The current population of a city = 83,700
The population of a city has increased by 35% since it was last measured.
We have to calculate the previous population before increasing 35%.
What is the meaning of population?
A population is a distinct group of individuals, whether that group comprises a nation or a group of people with a common characteristic.
Let the previous population be p
p +(35% × p) = 83,700
p + 0.35p = 83,700
p = 83,700
p = [tex]\frac{ 83,700}{1.35}[/tex]
p = 62,000
Therefore, the previous population was 62,000.
To learn more about the population visit:
https://brainly.com/question/25630111
#SPJ2
Please help me solve this quickly!
Answer:
33.80
Step-by-step explanation:
AB = BC = AD√2
AB = BC = 7√2
AD = DC
AC = 2AD
perimeter = AC + AB + BC
= 2AD + 2AB
= 2(7) + 2(7√2)
= 14 + 14√2
≈ 33.80
Answer:
33.8
Step-by-step explanation:
45-45-90 degree triangle rules states that the sides that are opposite the angles measure 45 degrees have the same value. That means that BD has the same value as AD, which is 7. Since triangle BDC is also a 45-45-90 degree triangle, DC is equal to BD, which is 7. We have the value of AC, which is 7+7=14. Now, we can use the Pythagorean theorem to figure out BC and AB. We know that [tex]DC^2+BD^2=BC^2[/tex]. We know that DC and BD is equal to 7, so we can simplify that to [tex]49+49=BC^2[/tex], and we can further simplify that to [tex]BC=\sqrt{98}[/tex]. This is also equal to [tex]7\sqrt{2}[/tex]. Since BC is also equal to AB because of 45-45-90 degree triangle rules, we have the perimeter of the triangle as
[tex]7\sqrt{2} + 7\sqrt{2}+14[/tex], which is equal to [tex]14\sqrt{2} + 14[/tex]. We can simplify 14 times the square root of 2 as 19.8 (rounded to 2 decimal places). We have the answer as 19.8 + 14, which is 33.8.
Help me pls!
The polygons in each pair are similar. Find the scale factor of the smaller figure to the larger figure
Answer:
Smaller figure: 1/3
Larger figure: 3
Answer:
1:3
Step-by-step explanation:
divided the sides
8/24 = 1/3 = 1:3
Find the standarddeviation of 125, 136, 150, 119, 150, and 143.
Answer:
S.D=46.04
Step-by-step explanation:
steps are in the picture.
If you have question about it you can ask.Thanks
can a triangle have two right angles ?explain
Answer:
a triangle is a closed polygon that consists of three sides and three angles,and it's one of the basic shape that we basic shape that we knowing geometry.
please solve this please
Answer:
C) [tex]\frac{2z+15}{6x-12y}[/tex]
E) [tex]\frac{7d+5}{15d^2+14d+3}[/tex]
F) [tex]\frac{-7a-b}{6b-4a}[/tex]
Step-by-step explanation:
C)
One is given the following equation
[tex]\frac{z+1}{x-2y}-\frac{2z-3}{2x-4y}+\frac{z}{3x-6y}[/tex]
In order to simplify fractions, one must convert the fractions to a common denominator. The common denominator is the least common multiple between the given denominators. Please note that the denominator is the number under the fraction bar of a fraction. In this case, the least common multiple of the denominators is ([tex]6x-12y[/tex]). Multiply the numerator and denominator of each fraction by the respective value in order to convert the fraction's denominator to the least common multiple,
[tex]\frac{z+1}{x-2y}-\frac{2z-3}{2x-4y}+\frac{z}{3x-6y}[/tex]
[tex]\frac{z+1}{x-2y}*\frac{6}{6}-\frac{2z-3}{2x-4y}*\frac{3}{3}+\frac{z}{3x-6y}*\frac{2}{2}[/tex]
Simplify,
[tex]\frac{z+1}{x-2y}*\frac{6}{6}-\frac{2z-3}{2x-4y}*\frac{3}{3}+\frac{z}{3x-6y}*\frac{2}{2}[/tex]
[tex]\frac{6z+6}{6x-12y}-\frac{6z-9}{6x-12y}+\frac{2z}{6x-12y}[/tex]
[tex]\frac{(6z+6)-(6z-9)+(2z)}{6x-12y}[/tex]
[tex]\frac{6z+6-6z+9+2z}{6x-12y}[/tex]
[tex]\frac{2z+15}{6x-12y}[/tex]
E)
In this case, one is given the problem that is as follows:
[tex]\frac{2}{3d+1}-\frac{1}{5d+3}[/tex]
Use a similar strategy to solve this problem as used in part (c). Please note that in this case, the least common multiple of the two denominators is the product of the two denominators. In other words, the following value: ([tex](3d+1)(5d+3)[/tex])
[tex]\frac{2}{3d+1}-\frac{1}{5d+3}[/tex]
[tex]\frac{2}{3d+1}*\frac{5d+3}{5d+3}-\frac{1}{5d+3}*\frac{3d+1}{3d+1}[/tex]
Simplify,
[tex]\frac{2}{3d+1}*\frac{5d+3}{5d+3}-\frac{1}{5d+3}*\frac{3d+1}{3d+1}[/tex]
[tex]\frac{2(5d+3)}{(3d+1)(5d+3)}-\frac{1(3d+1)}{(5d+3)(3d+1)}[/tex]
[tex]\frac{10d+6}{(3d+1)(5d+3)}-\frac{3d+1}{(5d+3)(3d+1)}[/tex]
[tex]\frac{(10d+6)-(3d+1)}{(3d+1)(5d+3)}[/tex]
[tex]\frac{10d+6-3d-1}{(3d+1)(5d+3)}[/tex]
[tex]\frac{7d+5}{(3d+1)(5d+3)}[/tex]
[tex]\frac{7d+5}{15d^2+14d+3}[/tex]
F)
The final problem one is given is the following:
[tex]\frac{3a}{2a-3b}-\frac{a+b}{6b-4a}[/tex]
For this problem, one can use the same strategy to solve it as used in parts (c) and (e). The least common multiple of the two denominators is ([tex]6b-4a[/tex]). Multiply the first fraction by a certain value to attain this denomaintor,
[tex]\frac{3a}{2a-3b}-\frac{a+b}{6b-4a}[/tex]
[tex]\frac{3a}{2a-3b}*\frac{-2}{-2}-\frac{a+b}{6b-4a}[/tex]
Simplify,
[tex]\frac{3a}{2a-3b}*\frac{-2}{-2}-\frac{a+b}{6b-4a}[/tex]
[tex]\frac{-6a}{6b-4a}-\frac{a+b}{6b-4a}[/tex]
[tex]\frac{(-6a)-(a+b)}{6b-4a}[/tex]
[tex]\frac{-6a-a-b}{6b-4a}[/tex]
[tex]\frac{-7a-b}{6b-4a}[/tex]
15. PLEASE HELP ME
A sports recreation company plans to manufacture a beach ball with a surface area of 7238 in.2 Find the radius of the beach ball. Use the formula A= 4\pir2, where A is the surface area and r is the radius of the sphere.
A. 48 in.
B. 24 in.
C. 75 in.
D. 576 in.
We know
[tex]\boxed{\sf Surface\:area=4\pi r^2}[/tex]
[tex]\\ \sf\longmapsto 4\pi r^2=7238[/tex]
[tex]\\ \sf\longmapsto 4\times \dfrac{22}{7}r^2=7238[/tex]
[tex]\\ \sf\longmapsto r^2=\dfrac{7238\times 7}{88}[/tex]
[tex]\\ \sf\longmapsto r^2=\dfrac{5066}{88}[/tex]
[tex]\\ \sf\longmapsto r^2=575.75[/tex]
[tex]\\ \sf\longmapsto r^2\approx576[/tex]
[tex]\\ \sf\longmapsto r\approx\sqrt{576}[/tex]
[tex]\\ \sf\longmapsto r\approx24in[/tex]
Option b is coreectAnswer:
B. 24 in.
Step-by-step explanation:
The given problem supplies as with the surface area of the beach ball and we are to look for the required radius. Assuming that the beach ball is perfectly shaped in the form of a sphere, then the formula for calculating the surface area of a sphere is given as:
SA = 4 π r^2
where r is the radius of the sphere and SA is the surface area which is given to be 7238 in^2
Rewriting the formula in terms of r:
r^2 = SA / 4 π
r = sqrt (SA / 4 π)
Solving for r:
r = sqrt (7238 in^2 / 4 π)
r = 24 in
Answer:
24 inches
Please answer this!!
Answer:
C, 5/12
Step-by-step explanation:
The tangent of an angle is defined as the side opposite to that angle divided by the side adjacent to that angle. The tangent of angle A would be equal to the value of side BC divided by side AB. The value of side BC is 5, and the value of side AB is 12. The answer is 5/12.
Answer: ∠A=[tex]\frac{5}{12}[/tex]
Step-by-step explanation:
Tangent is opposite over adjacent.
If the graph of f(x) = x^2, how will the graph be affected if it is changed to f(x) = 3r^2?
Answer:
the graph curve will goes above f(x)=x^2.f(x)=3*x^2 curve will also give higher value same value of x .
Step-by-step explanation:
Explain the
The fifth term of a non-linear sequence is 324. The term-to-term rule is ‘multiply by 3?
Work out the second term of the sequence.
Explain the method you used to solve this problem.
Answer:
a2=12 (the second term of the sequence is 12)
Step-by-step explanation:
a5=324
If the term to term rule is multiply by any number, we deal with geometrical sequence
The formula you should use is an= a1*r^(n-1) where n is the number of the term which we know. In our case we know
a5, so use 5 instead of n
Then you have a5=a1*r^4 where r is the number 3 (because each next term is greater than previous in 3 times)
a5=324
324= a1*3^4
324=a1*81
a1=4 (We find the first term of sequence, because having it you can easily search for every term )
Return to the formula an= a1*r^n-1
Now search for the second term using 2 instead of n in the formula
a2= a1*r^1
a2=a1*r, a1=4, r=3
a2=4*3=12
A student states that Figure JKLM is congruent to Figure PQRS. Determine if the student is correct or has made an error. ;D
Answer:
Student has made an error
Step-by-step explanation:
If two figures are said to be congruent, this implies that area of both is same and both as exactly same or copy or each other.
But from the graph, it can be stated that height of figure JKLM is 4 units whereas that of other is 6 unit.
Hence explained !
HELP PLS HELP MEEEEE IM FAILING PYTHAGOREAN THEOREM
7^2 + 6^2 = h^2
49 + 36 = h^2
85 = h^2
√85 = h
h = 9.21m
Answered by Gauthmath must click thanks and mark brainliest
Hii, please help me with this question I keep getting an option that isn't there.
A cylindrical piece of iron pipe is shown below. The wall of the pipe is 1.25 inch thick:
The figure shows a cylinder of height 16 inches and diameter 6 inches.
What is the approximate inside volume of the pipe?
a. 88 cubic inches
b. 49 cubic inches
c. 142 cubic inches
d. 154 cubic inches
The volume of this pipe considering the thickness of the pipe is 154 cubic inches.
How do you calculate the volume of the pipe?The general formula to calculate the volume of a cylindric object such as a pipe is:
V = πd^2h/4In this formula, d represents the diameter and h represents the height.
What is the diameter?The external diameter is 6 inches; however, the pipe is 1.25 inches thick, which implies the real internal diameter is 3.5.
6 inches - 2.5 (1.25 x 2) = 3.5Now, let's calculate the volume:
V = πd^2h/4V= π (12.25 x 16)/4V= π (196)/4V= 615.713 / 4 = 153.93 which can be rounded as 154 cubic inches.Learn more about cylindric in: https://brainly.com/question/14965384
Answer:
D. 154 cubic inches
Step-by-step explanation:
Guys please help me solve this problem, yes I will mark brainliest
Given that the vertex is at (50, 1000), the max profit is $1000 when 50 items are produced
In the picture below, which lines are lines of symmetry for the figure?
(PICTURE) Can someone please help me out Im reporting trolls. Marking brainliest
Answer:
smart dot company would be c=.50t+12
communication plus would be c=2.50t
Step-by-step explanation:
smart dot starts with $12 a month and adds $0.50 for each hour of internet use. communication plus has no starting fee so it just adds $2.50 for each hour of internet use.
So then for the table you would put the number given for time in for the letter t and find what c would be. This would then find your cost for that amount of hours. To get you started smart dot company starts off with 0 hours so put that in for t being c=0.50(0)+12 and c=12. Communication plus also starts with 0 so it would be c=2.50(0) and c=0
Then you graph once you have both values you can graph having x=time and y=cost
Let me know if this helps!
please anyone give me a answer i need it rn
Answer:
The first option is the right one.
Step-by-step explanation:
7/2. Rate is rise/run
7 is your rise
and 2 is your run
therefore, the answer is 7/2
Two consecutive integers have a sum of 107. Find the integers.
Answer: 53 and 54
Explanation
Let the consecutive numbers be x and x + 1
ATQ
x + x + 1 = 107
2x = 107 - 1
x = 106/2
x = 53
Therefore the numbers are 53 and 54
Must click thanks and mark brainliest
Answer:
x = 53, x + 1 = 54
Step-by-step explanation:
Consecutive integers are two numbers that are after each other. (This is confusing wording, but hopefully this example helps):
Regular consecutive numbers: 1, 2, 3
Even consecutive numbers: 2, 4, 6
Since in this problem the numbers are not given you will use variables.
x + x + 1 = 107
Solve:
x + x + 1 = 107
2x + 1 = 107
-1 -1
----------------
2x = 106
--- -----
2 2
x = 53
x + 1
53 + 1 = 54
Hope this helped.
18-3×5+32÷4
USE BODMAS RULE
the answer should come 11
Answer:
B-bracket
O-of
D-division
M-multiplication
A-addition
S-subtraction
Step-by-step explanation:
18-3×5+32÷4
18-3×5+8 (by dividing 32 by 4 = 8)
18-15+8(by multiplying 3×5=15)
18-7( by -15 +8= 7 )
11
hence proved
11 is the answer by BODMAS rule .
hope this helps you
mrk me braniliest
A textbook store sold a combined total of 240 chemistry and history textbooks in a week. The number of chemistry textbooks sold
was two times the number of history textbooks sold. How many textbooks of each type were sold?
Answer:
160 chemistry books and 80 history books
Step-by-step explanation:
C=chemistry books sold, H=history books sold
C=2H
C+H=240, 3H=240, H=80, C=160
x.(9x-1).(x+2)-x(3x-1).(3x+1)
Answer:
=17x²-x
Step-by-step explanation:
=x.(9x²+18x-x-2)-x.(9x²-1)
=x.(9x²+17x-2-9x²+1)
=x.(17x-1)
=17x²-x
I need help for this question 3 so can anyone help me please
How would the expression x^2 -9 be rewritten using Difference of Squares?
O A. (x+3)(x - 3)
O B. (X-9)^2
O C. (x +9)(x-9)
O D. (x+3)^2
Answer:
A. (x+3)(x - 3)
Step-by-step explanation:
x^2 -9
Rewriting
x^2 - 3^2
We know that a^2 - b^2 = (a-b)(a+b)
(x-3)(x+3)
Answer:
[tex]\left(x+3\right)\left(x-3\right)[/tex]
Step-by-step explanation:
[tex]x^2 -9[/tex]
To factor an integer, we need to divide it by the ascending sequence of primes (2, 3, 5). The number of times each prime divides the original integer becomes its exponent. [tex]3^{2} =9[/tex]
Now, we need to factor this expression by applying the difference of two squares rule:
[tex]A^{2} -B^{2} =(A+B)(A-B)[/tex]
A= x and B= 3
[tex](x+3)(x-3)[/tex]
OAmalOHopeO
See pic below! Need help solving
Answer:
383.54 m
Step-by-step explanation:
The length of the training track running around the field = circumference of the circle formed by the two semicircles + 2(length of the rectangle)
The two semicircles forms a fill circle with diameter (d) = width of rectangle = 61 m
Length of rectangle (L) = 96 m
π = 3.14
The length of the training track running around the field = πd + 2(L)
Substitute the values
The length of the training track running around the field = 3.14*61 + 2(96)
= 191.54 + 192
= 383.54 m
What is the equation of the graph?
Answer:
In the sciences, many times it is necessary to be able to interpret graphs as well as be able to graph certain equations. Often data is available in a graphical format and you must be able to extract the necessary information. Other times, it may be helpful to plot an equation in order to fully understand a problem. However, graphing can be difficult for some students. The format in this section is a little different. The first part will be simply showing what some special equations look like in graphical form and the second part will be a series of questions to help you understand graphs better.
Step-by-step explanation:
Given: m∠V=103°, m∠VRT=71°, RS ∥ VU Find: m∠TRS, m∠U
Answer:
m∠TRS = 6°
m∠U = 103°
Step-by-step explanation:
In the given figure,
O is the center
RS ∥ VU
m∠V = 103° &
m∠VRT = 71°
So,
m∠V + m∠R = 180° (∵ sum of co-interior angles)
⇒ m∠R = 180° - 103° (m∠V = 103° is given)
∵ m∠R = 77° ...(i)
Now,
m∠R = m∠TRS + m∠VRT
by putting the values given
⇒ m∠TRS = 77° - 71°
∵ m∠TRS = 6°
As we know that,
VURT is a cyclic quadrilateral. So,
m∠U + m∠R = 180°
⇒ m∠U + 77° = 180° (from equation (i)
∵ m∠U = 180° - 77° = 103°
x>0, y>0, 2x+3y=8, smallest value of xy? pls help me
Answer:
where there is x in the equation we put 0
For y
=2(0)+3y=8
=0+3y=8 Group likely terms
=3y=8-0
=3y=8 Divide both sides by 3
=3y/3=8/3
Therefore y=2.6
For x
=2x+3y=8
=2x+3(0)=8
=2x+0=8 Group likely terms
=2x=8-0
=2x=8 Divide both sides by 2
=2x/2=8/2
Therefore x=4
The smallest numbers for x and y is 4 and 2.6 respectively
Please help explanation if possible
that's the answer pls mark as brainliest
Answer:
x = 71 and y = 19
Step-by-step explanation:
Given the 2 equations
x + y = 90 → (1)
x = 14 + 3y → (2)
Substitute x = 14 + 3y into (1)
14 + 3y + y = 90 ( subtract 14 from both sides )
4y = 76 ( divide both sides by 4 )
y = 19
Substitute y = 19 into (1) for value of x
x + 19 = 90 ( subtract 19 from both sides )
x = 71
Larger number x = 71 ; Smaller number y = 19
Write the equation of the line with a slope of 4 that contains the point (5, 8).
Answer:
y = 4x - 12
Step-by-step explanation:
y = 4x + b
8 = 4(5) + b
8 = 20 + b
-12 = b
[tex] \green{ \boxed{\boxed{\begin{array}{cc} \maltese \bf \: \: \: we \: know \: that \: \\ \sf \: if \: any \: equation\:of \: line \: which \: slope (m) \\ \sf \: and \: passes \: through \: (x_1,y _1) \: \: then \: its \\ \sf equation \: is \: : \\ \\ \red{ \boxed{ \bf y - y_1 = m(x - x_1)}}\bf\end{array}}}}[/tex]
Given that,
A equation of the line with a slope of m = 4 and that contains / passes through the point (5, 8).
So,
[tex] \green{ \boxed{\boxed{\begin{array}{cc} \bf \: x_1 = 5 \: \: \: \\ \bf y_1 = 8 \\ \bf \: m \: = 4 \: \: \end{array}}}}[/tex]
NOW,
The equation is :
[tex] \green{ \boxed{\boxed{\begin{array}{cc} \bf \: y - 8 = 4(x - 5) \\ \\ = > \bf \: y - 8 = 4x - 20 \\ \\ = > \pink{ \boxed{\bf\:4x - y - 12 = 0}} \end{array}}}}[/tex]
Which best describes the relationship between the lines with equations −6x+8y=−1 and −4x−3y=2?
Answer:
it is linear
Step-by-step explanation:
Both of these both lines are perpendicular to each other.
We have the two equations of straight lines :
− 6x + 8y = −1 and −4x − 3y = 2.
We have to identify the relation between these two lines.
What is the general equation of a straight line ?The general equation of a straight line is as follows -
y = mx + c
where -
m - slope of line
c - intercept of line on y - axis.
According to the question, we have -
−6x + 8y = −1 ...(1)
−4x − 3y = 2 ...(2)
Rearranging the terms of the equations we get -
y = [tex]\frac{3}{4} x - \frac{1}{8}[/tex] ...(3)
and
y = [tex]\frac{-4}{3}x - \frac{2}{3}[/tex] ...(4)
When compared -
The slope of line −6x + 8y = −1 is m(1) = [tex]\frac{3}{4}[/tex].
The slope of line −4x − 3y = 2 is m(2) = [tex]\frac{-4}{3}[/tex].
We can see that -
m(1) x m(2) = - 1
The product of the slopes of two perpendicular lines is -1.
Hence, these both lines are perpendicular to each other.
To solve more questions on relation between straight lines, visit the link below -
brainly.com/question/13792781
#SPJ2